The mediating effect of attitudes toward genetic testing on the relationship between genetic knowledge of familial hypercholesterolemia and the intention to undergo genetic testing among patients with hyperlipidemia in Korea: a cross-sectional study - Minji Kim; Myoungock Jang (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study examined whether attitudes toward genetic testing mediated the relationship between genetic knowledge of familial hypercholesterolemia (FH) and intention to undergo genetic testing among patients with hyperlipidemia. Methods: This descriptive correlational, cross-sectional study included 140 adults with hyperlipidemia. Participants completed self-report questionnaires assessing genetic knowledge of FH, positive and negative attitudes toward genetic testing, and intention to undergo genetic testing. Data were analyzed using Pearson correlation analysis, multiple linear regression, and PROCESS Macro Model 4. Results: Multiple regression analysis showed that family history in a sibling (β = .20, p = .011), positive attitudes toward genetic testing (β = .41, p < .001), and negative attitudes toward genetic testing (β = -.24, p = .006) were significantly associated with the intention to undergo genetic testing. While the total effect of genetic knowledge on the intention was not significant (BootB = 0.04, 95% confidence interval [CI] [-0.001, 0.081]), positive attitudes toward genetic testing significantly mediated the relationship between genetic knowledge of FH and the intention to undergo genetic testing (direct effect = 0.03, p = .177; indirect effect = 0.01, 95% CI [0.001, 0.031]). Negative attitudes toward genetic testing did not mediate the relationship. Conclusion: Positive attitudes toward genetic testing were a significant mediator of the relationship between genetic knowledge of FH and intention to undergo genetic testing. These findings suggest that interventions intended to promote genetic testing should address patients’ positive attitudes toward testing rather than rely solely on information provision.